A century in synonymy: molecular and morphological evidence for the revalidation of Glyptosternon osсhanini (Herzenstein, 1889) (Actinopterygii: Sisoridae) - Thoni, Ryan J.; Simonov, Evgeniy; Artaev, Oleg; Asylbaeva, Shaigul; Aibek, Sergek Uulu; Levin, Boris A. (Zootaxa, 2017)
Exostoma oschanini, presently treated as a junior synonym of Glyptosternon reticulatum, is revalidated within Glyptosternon based on a phylogenetic analysis of the CO1 gene and morphological characters. Glyptosternon oschanini is known to occur in tributaries of the Syr Darya River in Uzbekistan and Kyrgyzstan and may also occur in the Amu Darya River drainage. A morphological diagnosis and description are provided for G. oschanini. Exostoma gracile is a junior synonym of G. oschanini rather than of G. reticulatum.